High efficacy of interferon-free therapy for acute hepatitis C in HIV-positive patients. Issue 4 (May 2019) - Chromy, David; Mandorfer, Mattias; Bucsics, Theresa; Schwabl, Philipp; Scheiner, Bernhard; Schmidbauer, Caroline; Aichelburg, MC; Ferenci, Peter; Trauner, Michael; Peck-Radosavljevic, Markus; Reiberger, Thomas
Background: The treatment of acute hepatitis C (AHC) with direct-acting antiviral agents (DAAs) is considered a cornerstone of hepatitis C virus (HCV) elimination strategies, especially in human immunodeficiency virus (HIV)-infected individuals at high risk of onward transmission. Objective: Optimal treatment regimens and duration for AHC in HIV-coinfected patients remain to be established. Thus, we aimed to evaluate the efficacy and safety of DAA treatment regimens in the setting of AHC. Methods: All HIV-positive patients with a diagnosis of AHC according to the European AIDS Treatment Network (NEAT) consensus attending our clinic after 2014 were included. DAA treatment regimens and duration were based on current recommendations for chronic hepatitis C (CHC) at treatment initiation. Results: Thirty-eight HIV/AHC patients (median age 42.0 years), mostly men who have sex with men (92%), were started on interferon-free regimens. HCV-genotype (GT) was predominately GT-1a (65%). The following DAA regimens were prescribed: ombitasvir/paritaprevir/ritonavir/dasabuvir (42%; 16/38), glecaprevir/pibrentasvir (29%; 11/38), sofosbuvir/ledipasvir (13%; 5/38), ombitasvir/paritaprevir/ritonavir (5%; 2/38), grazoprevir/elbasvir (5%; 2/38) and sofosbuvir/velpatasvir (5%; 2/38). All HIV/AHC patients achieved sustained virologic response 12 weeks after end of treatment (SVR12) (100%; 38/38). DAA-related adverse events were rare. Conclusion: Interferon-free DAA regimens (including 34% pan-genotypic regimens) yielded 100% SVR12 in HIV/AHC individuals if treatment durations similar to CHC are applied.